Incidence of apical crack formation and propagation during removal of root canal filling materials with different engine driven nickel-titanium instruments - Taha Özyürek; Vildan Tek; Koray Yılmaz; Gülşah Uslu (Korean Academy of Conservative Dentistry, 2017)
Objectives To determine the incidence of crack formation and propagation in apical root dentin after retreatment procedures performed using ProTaper Universal Retreatment (PTR), Mtwo-R, ProTaper Next (PTN), and Twisted File Adaptive (TFA) systems. Materials and Methods The study consisted of 120 extracted mandibular premolars. One millimeter from the apex of each tooth was ground perpendicular to the long axis of the tooth, and the apical surface was polished. Twenty teeth served as the negative control group. One hundred teeth were prepared, obturated, and then divided into 5 retreatment groups. The retreatment procedures were performed using the following files: PTR, Mtwo-R, PTN, TFA, and hand files. After filling material removal, apical enlargement was done using apical size 0.50 mm ProTaper Universal (PTU), Mtwo, PTN, TFA, and hand files. Digital images of the apical root surfaces were recorded before preparation, after preparation, after obturation, after filling removal, and after apical enlargement using a stereomicroscope. The images were then inspected for the presence of new apical cracks and crack propagation. Data were analyzed with χ2 tests using SPSS 21.0 software. Results New cracks and crack propagation occurred in all the experimental groups during the retreatment process. Nickel-titanium rotary file systems caused significantly more apical crack formation and propagation than the hand files. The PTU system caused significantly more apical cracks than the other groups after the apical enlargement stage. Conclusions This study showed that retreatment procedures and apical enlargement after the use of retreatment files can cause crack formation and propagation in apical dentin.